2017
DOI: 10.1039/c7ra11005g
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the regioselectivity of Michael addition reactions to asymmetric divinylic compounds

Abstract: aIn the present paper, we describe the synthesis of novel monomers prepared by regioselective Michael addition to asymmetric divinylic compounds. This chemoselectivity was experimentally studied employing different reaction conditions and theoretically calculated using chemical global and local descriptors. The global reactivity data show that incoming nucleophilic secondary amines preferentially attack the acrylic derived units acrylate and acrylamide, while deactivated methacrylate and N-vinyl-pyrrolidone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, still no well‐defined film was observed (Figure S1a, Supporting Information). This trend in the solidification performance matches the general observation that free radical polymerization propagation kinetics are higher with acrylate monomers when compared to methacrylates that contain similar pendant groups . Finally, the ink formulation was further improved by replacing IBHEMA with ibuprofen attached hydroxyethyl acrylate (IBHEA), such that an acrylate‐based reactive linker was used.…”
Section: Resultssupporting
confidence: 63%
“…However, still no well‐defined film was observed (Figure S1a, Supporting Information). This trend in the solidification performance matches the general observation that free radical polymerization propagation kinetics are higher with acrylate monomers when compared to methacrylates that contain similar pendant groups . Finally, the ink formulation was further improved by replacing IBHEMA with ibuprofen attached hydroxyethyl acrylate (IBHEA), such that an acrylate‐based reactive linker was used.…”
Section: Resultssupporting
confidence: 63%
“…In contrast to other complicated organic modifications, the basic structure of Michael acceptors, such as acrolein, can form covalent bonds with multiple target sites by a nonspecific process [ 20 , 21 , 22 ]. The specificities of Michael addition are dependent on the 3D structure and electrophilicity of β-carbon and the functional groups of Michael acceptors [ 23 ]. Although the various pairs of acceptors and nucleophiles of Michael addition provide diverse prospects in the development of organic synthesis and materials science, it results in many challenges in clinical medicine, especially in drug discovery because of high costs incurred, owing to the labor required and the complicated experiments that are performed.…”
Section: Michael Additionmentioning
confidence: 99%
“…The reaction was performed using 0.0017 mol of MHU and 0.0008 mol of HMD, which indicated an excess of 0.125, whereas the relation of A methacrylate /A alkene was calculated as 0.320; thus, a conversion of 80.5% was obtained after this reaction. Navarro et al 46 performed a reaction between 2-(acryloyloxy)ethyl methacrylate and dibutylamine in chloroform at 40 °C for 3 h, resulting in a conversion of 85%. Wu et al 59 observed that the reactivity of amines changed during Michael addition polymerization of diacrylates with trifunctional amines.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%